Pathophysiology of high fat diet induced obesity: impact of probiotic banana juice on obesity associated complications and hepatosteatosis - Prabhakar Yellanur Konda (Nature Portfolio, 2020)
Abstract The high fat diet alters intestinal microbiota due to increased intestinal permeability and susceptibility to microbial antigens leads to metabolic endotoxemia. But probiotic juices reported for various health benefits. In this background we hypothesized that pectinase treated probiotic banana juice has diverse effects on HFD induced obesity and non-alcoholic steatohepatitis. 20 weeks fed HFD successfully induced obesity and its associated complications in experimental rats. The supplementation of probiotic banana juice for 5 months at a dose of 5 mL/kg bw/day resulted significant decrease (p < 0.05) in body weight (380 ± 0.34), total fat (72 ± 0.8), fat percentage (17 ± 0.07) and fat free mass (165 ± 0.02). Reduction (p < 0.05) in insulin resistance (5.20 ± 0.03), lipid profile (TC 120 ± 0.05; TG 160 ± 0.24; HDL 38 ± 0.03), liver lipid peroxidation (0.7 ± 0.01), hepatic enzyme markers (AST 82 ± 0.06; ALT 78 ± 0.34; ALP 42 ± 0.22), and hepatic steatosis by increasing liver antioxidant potential (CAT 1.4 ± 0.30; GSH 1.04 ± 0.04; SOD 0.82 ± 0.22) with normal hepatic triglycerides (15 ± 0.02) and glycogen (0.022 ± 0.15) contents and also showed normal liver size, less accumulation of lipid droplets with only a few congestion. It is concluded that the increased intestinal S. cerevisiae yeast can switch anti-obesity, antidiabetic, antioxidative stress, antioxidant and anti-hepatosteatosis effect. This study results will have significant implications for treatment of NAFLD.